NIGERIAN PUBLIC AWARENESS AND KNOWLEDGE OF THE MILLENNIUM DEVELOPMENT GOALS (MDGs) AND THEIR LEVEL OF IMPLEMENTATION IN NIGERIA - Ogbodo, Jude Nwakpoke; Okoro, Nnanyelugo M. (European Scientific Journal, ESJ, 2015)
This study was aimed at assessing the status of Nigerian public awareness and knowledge of the Millennium Development Goals (MDGs) and their level of implementation in Nigeria. Survey research design was used to this effect. Contrary to speculations from all quarters that Nigeria is on the verge of achieving the MDGs, this study revealed that the level of implementation of MDGs in Nigeria is still at its lowest ebb. Based on the findings, it is recommended that Nigerian government should as a matter of necessity and urgency, select and pursue vigorously at least four of the goals that are manageable and more critical than others instead of pursuing all at the same time and losing all at the end. It will make sense if all impediments hampering the achievement of the MDGs are removed and very quickly too.